تشخيص المفاهيم الخاطئة في الرياضيات لدى طالبات الصف الثاني المتوسط - ا .د. فائق فاضل احمد السامرائي,; بشار احمد سلطان, (مجلة الفتح للبحوث التربوية والنفسية, 2023)
ملخص البحث : ھدفت الدراسة الى تشخیص المفاھیم الخاطئة في الریاضیات لدى طالبات الصف الثاني المتوسط ، ولغرض تحقیق ھدف الدراسة قام الباحثان بتحلیل محتوى الفصول الاربعة الاولى من كتاب الریاضیات للصف الثاني المتوسط الخاضعة لتجربة البحث ، لتحدید المفاھیم الریاضیة الواردة فیھا. وقد بلغ عدد المفاھیم (٤٩ (مفھوماً بعد اخذ موافقة (٨٠ (%فأكثر من اراء الخبراء فیھا، اعد الباحثان على اساسھا اختباراً تشخیصیاً موضوعیاً من نوع الاختیار من متعدد رباعي البدائل ، یتم فیھ قیاس اكتساب كل مفھوم ریاضي من خلال ثلاثة مجالات (ترجمة ، تفسیر ، استكمال ) ، وبذلك بلغ عدد فقراتھ (١٤٧ ( فقرة ، تقیس كل ثلاث فقرات متتالیة مفھوماً ریاضیاً واحداً وتم التحقق من صدقھ وثباتھ وفاعلیة بدائلھ ثم طبق الاختبار على عینة مكونة من (١٠٠ (طالبة ، وعلى اساس ھذه الاختبار تعد المفاھیم ذات فھم خاطئ اذا تجاوزت نسبة الخطأ فیھا (٣٤ %) فاكثر لدى طالبات عینة التشخیص ، ومن خلال نتائج الاختبار تبین ان ھناك (٢٨ (مفھوماً ذات فھم خاطئ. Diagnosis of misconceptions in mathematics with average second grade students Research Summary The study aimed to diagnose misconceptions in mathematics with average second grade students, and for the purpose of achieving the objective of the study the researchers analyzed the content of the first four chapters of the book for the second grade math average, to determine the mathematical concepts contained therein.The number of concepts (49) after taking the approval of the concept (80%) or more of the views of the experts, researchers prepared on the basis of which an objective diagnostic test of choice type of multi-quadrant alternatives, which measure the gain of each athlete concept through three العدد الرابع والخمسون . مجلة الفتح . تموز لسنة ٢٠١٣ أ.د. فائق فاضل احمد بشار احمد سلطان -٢- areas (translation, explanation, complete), bringing the number of paragraphs (147) vertebra, measure all three paragraphs consecutive understood mathematically one was verified sincerity and firmness and effectiveness of alternatives, then applied the test on a sample of 200 students, and on the basis of this test are concepts misconception if the error rate exceeded (34%) and more with the students sample diagnosis, and through the test results show that there are (28) concept of a .misunderstanding